Facebook as an educational tool in the university context - Iglesias García, Mar; González Díaz, Cristina (Historia y Comunicación Social, 2014)
This research studies the use of Facebook by students in first course of Advertising Communication and Public Relations (University of Alicante) to learn the subject Communication and Media Writings. The methodology used is the survey of 76 students during the month of January 2013. The results show an improvement of the teaching-learning process. The social media used to share materials, practices and answer questions encouraging collaborative learning. Students agree that the benefit involves the use of Facebook to learn the subject.